Starten på arbeidet med skolehager i Norge – Andreas M. Feragens hage i Holt på Agder - Jahr, Ernst Håkon (Scripta Neophilologica Posnaniensia, 2021)
This paper recounts the beginnings of the School Gardening Movement in Norway, which is now (in 2021) a topic of great interest throughout the country. The famous 19th-century school teacher and reformist Andreas M. Feragen (1818–1912), who retired from his teaching position at the age of 93, was the first to argue, in the late 1850s and early 1860s, for including gardening both as a subject and as a practical activity in primary schools. A widely used reader first published in 1863 included four pieces by Feragen about different types of gardens which would be appropriate for a rural school: the first piece was about the garden in general, the following three described a kitchen garden, a fruit garden, and a flower garden. These four pieces were written in the form of a story about a teacher and his students strolling around the gardens discussing what they saw and how to grow vegetables, fruit trees and fruit bushes, and flowers. Feragen followed up these pieces with an article in the teachers’ journal Den norske Folkeskole [The Norwegian Primary School] in which he argued that basic gardening knowledge ought to be included in the teacher training curriculum. School gardening in Norway started with Feragen’s own gardens surrounding his school in Holt in Agder, clearly the very gardens he described in his pieces in the reader.